Consciência política e participação dos representantes da sociedade civil do Conselho Municipal de Assistência Social de Vitória (ES) - Dau, Arthur Gomes (2017)
The management councils, participatory mechanisms included in the legal framework of the Brazilian State by the Federal Constitution of 1988, became the main instrument alignment between direct interests of civil society and the government. It was created